2011
DOI: 10.1113/expphysiol.2010.055970
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic mechanisms underpinning the stress response in borderline hypertensive rats

Abstract: This study investigates blood pressure (BP) and heart rate (HR) short-term variability and spontaneous baroreflex functioning in adult borderline hypertensive rats and normotensive control animals kept on normal-salt diet. Arterial pulse pressure was recorded by radio telemetry. Systolic BP, diastolic BP and HR variabilities and baroreflex were assessed by spectral analysis and the sequence method, respectively. In all experimental conditions (baseline and stress), borderline hypertensive rats exhibited higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 60 publications
4
17
0
Order By: Relevance
“…3,17 Furthermore, a study using an animal model has provided direct confirmation that stress exposure plays a causal role in the pathogenesis of hypertension. 18 We observed increased HR in the first minute and after MST in relation to the HR at rest only in the OH group. Previous studies have also demonstrated that offspring of hypertensive parents submitted to an Arithmetic Test or to an Cold Pressor Test presented increased cardiovascular responses.…”
Section: Discussionmentioning
confidence: 80%
“…3,17 Furthermore, a study using an animal model has provided direct confirmation that stress exposure plays a causal role in the pathogenesis of hypertension. 18 We observed increased HR in the first minute and after MST in relation to the HR at rest only in the OH group. Previous studies have also demonstrated that offspring of hypertensive parents submitted to an Arithmetic Test or to an Cold Pressor Test presented increased cardiovascular responses.…”
Section: Discussionmentioning
confidence: 80%
“…However, young SHR are not a suitable model for representing essential prehypertension in adulthood due to the early onset of fully developed hypertension (i.e., systolic BP over 140 mm Hg) before reaching adulthood (~12 weeks of age) [10]. A more appropriate genetic model of essential prehypertension consists of borderline hypertensive rats (BHR), which were obtained by the mating of female SHR and male normotensive Wistar-Kyoto (WKY), resulting in a systolic BP of approximately 140 mm Hg in the adulthood stage [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…During the experiments, the animals were exposed to two types of stress: shaker stress, with rats positioned on a platform shaking at 200 cycles/min, and restraint stress, with rats placed in a Plexiglas restrainer tube (ID 5.5 cm with pores) in the supine position, with a detailed description given in [24]. These data were already used for other research purposes [20,24,25]. The duration of records in baseline, restraint stress, and shaker stress was 20 minutes, 60 minutes, and 20 minutes, respectively.…”
Section: Experimental Datamentioning
confidence: 99%